Experiences in Continuing Innovative Biomedical Research Amidst the Covid-19 Pandemic (Memorias Sifored - Encuentros Educación UAN, 2021)
The COVID-19 pandemic has brought unprecedented challenges for the world in every field. The academic sector has faced new challenges during this pandemic and the response of researchers, administrative workers and the student body has been remarkable, allowing education to remain an unstoppable journey and universities to continue as the birthplace of innovative science. At the University of Oklahoma, research and education have remained active by establishing strict, detailed protocols that aim to keep researchers and students safe while maintaining the academic momentum. In this paper, we present our experience at the Biomechanics and Biomaterials Design Laboratory (BBDL) under the ongoing COVID-19 pandemic. In our research group, productivity and student mentoring remained strong and eager despite university shutdowns and local regulations. By establishing in-lab protocols regulations to control the spread of the virus and by promoting contactless communications and scientific discussion, the BBDL has been able to continue to execute research projects in cardiovascular biomechanics, aneurysm therapeutic device design, and vascular tissue engineering. From literature reviews to virtual conference presentations, journal publications and biomedical device development, the BBDL has been able to produce research results and promote undergraduate professional development during these difficult times. In hopes of promoting a collaborative environment both locally and internationally, we present the lessons we have learned during the COVID-19 outbreak, outcomes of our experience and the current and future challenges for research and education.